GENERATOR SETS PRESENTATION OF INFORMATION USING PT.TRANSAVINDO PERSADA SEJAHTERA MICROSOFT FRONTPAGE 2000 - Satrio Purwanto; Drs. Sunarto Usna, MMSI (Jurnal Sistem Informasi, 2004)
Website created using Microsoft FrontPage to introduce the company, providing information such as gensets procurement services, consulting services, repair services, maintenance and improve service to its customers. With the Web built this business so PT.Transavindo Sejahtera Persada convince the community about services served by HR ajajran berkulitas of directors, management, staff specialists, mechanic / mechanic and employees who are selected for competency in their own fields.